2009
DOI: 10.1007/s00542-009-0930-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of novel electrical routing and integrated packaging on bio-compatible flexible substrates

Abstract: Electrical routing and integrated packaging on bio-compatible flexible substrates have been designed and fabricated. The realized packaging method can integrate electrical circuits, stationary components and moving components on flexible substrates. Chips can be embedded on flexible packages and work on a non-planar surface. In this article, the package specimens are tested and simulated in tensile, bending and sealing experiments. In addition, the density and Young's Modulus of polydimethylsiloxane (PDMS) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 12 publications
5
29
0
Order By: Relevance
“…[0. [1][2][3][4] MPa [30], that would increase the applications spectrum of the material. As a consequence it remains very difficult to find a complete study where fabrication recipes and mechanical properties, over a large domain of applications, are brought together.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[0. [1][2][3][4] MPa [30], that would increase the applications spectrum of the material. As a consequence it remains very difficult to find a complete study where fabrication recipes and mechanical properties, over a large domain of applications, are brought together.…”
Section: Introductionmentioning
confidence: 98%
“…Much work has been done into the investigation of the mechanical properties of PDMS and their potential tunability [26,28,21,29,30,16,31,32,17,33,4,[34][35][36][37]. The largest observed tensile stiffness, using 10:1 PDMS, to date is less than 4 MPa [30] after 7 days post-baking at 100 • C and less than 3 MPa for post-baking at 200 • C during 18 min [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the amplitude of the peak did not correlate to the changes in flow level. This peak could be varied by adjusting the mechanical properties of the fluidic system either by changing the curing method of the PDMS as described by Hong et al 30 or modifying the tubing (material or size) used in the system. Preliminary studies were conducted to verify this hypothesis, and the low-frequency peak was able to be shifted from 0.833 to 0.55 Hz at a constant perfusion level of 1 ml∕ min ∕g by using a more compliant phantom.…”
Section: Discussionmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) is a material that has been extensively investigated for use in many biodevices because it is biocompatible, flexible, and stretchable [26][27][28][29]. For example, Xu et al reported stretchable light emitting diodes with strain sensors, with AgNWs embedded in a PDMS substrate.…”
Section: Introductionmentioning
confidence: 99%